Pastoral care as community care : towards an intergrative approach to healing and well-being within the HIV and AIDS discourse - Mouton, Dawid Petrus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2012.